Kentucky history collection - Clore, Julia Alves
Letters, documents, clippings, portraits, and printed matter relating to the history of Kentucky. Individuals represented in the collection include Walter Alves, Thomas Hart Benton, R.S. Blount, Nathaniel Harte, Richard Henderson, James Hogg, Samuel Goode Hopkins, and William Johnston.
Selected items available on microfilm only
Microfilm produced with permission of Julia Alves Clore.
Positive photostats.
Collector.
Collection material in English.
Keywords: Alves, Walter, -- 1768-1819.; Benton, Thomas Hart, -- 1782-1858.; Blount, R. S; Harte, Nathaniel; Henderson, Richard, -- 1735-1785.; Hogg, James; Hopkins, Samuel Goode; Johnston, William, -- of Kentucky; Kentucky -- History